Low pressure gas discharge in magnetically insulated diode - Jamirzoev, A.; Yakovin, S.; Zykov, A. (Вопросы атомной науки и техники, 2015)
The characteristics of the low pressure discharge in crossed electric and magnetic fields is described in this work for the case of magnetically insulated diode and electron anode layer with free cathode boundary. The theory is compared with experimental characteristics of Hall-type ion source “Radical” such as breakdown curves, current-voltage characteristics, dependences of discharge current on magnetic field and pressure. As a result of the carried out analysis, the mechanism of the discharge evolution dependence on boundary conditions is proposed. The mechanism of discharge initiation based on combined ionization of gas by electron avalanches and high energy γ-electrons is considered as well.